Metaphorical modelling of cognitive structure of the concept STINGINESS in British, German, Ukrainian and Russian linguocultures - Mizin, Kostiantyn; Petrov, Olexandr (Przegląd Wschodnioeuropejski, 2017)
This article deals with determining peculiarities of metaphorical modelling of cognitive structure of the concept STINGINESS in British, German, Ukrainian and Russian linguocultures by the way of analysing phraseological objectivation of the concept in the light of the relevant contrastive-linguoculturological approach. The authors establish that mainly common metaphoric models lie at the basis of the metaphors representing the concept STINGINESS. It is determined that despite the prevalence of metaphors containing common meaning of stinginess in the researched linguocultures distinct prevalence of common cognitive features over the specific ones within the metaphors themselves (metaphoric models), the concept STINGINESS is largely filled with ethnically and linguoculturally specific meanings in the contrasted language communities, that is proved by the metaphors STINGINESS IS ILLUSION by British and Germans, STINGINESS IS MEANNESS by British, STINGINESS IS SHAME by Ukrainians, STINGINESS IS NOT A FULLISH THING by Ukrainians and Russians. It is noteworthy that most of the conceptual metaphors representing the concept STINGINESS are commonly found in all the four linguocultures.